2013
DOI: 10.1016/j.cub.2013.04.049
|View full text |Cite
|
Sign up to set email alerts
|

Fluid Shear Stress on Endothelial Cells Modulates Mechanical Tension across VE-Cadherin and PECAM-1

Abstract: Summary Fluid shear stress (FSS) from blood flow acting on the endothelium critically regulates vascular morphogenesis, blood pressure and atherosclerosis [1]. FSS applied to endothelial cells (EC) triggers signaling events including opening of ion channels, activation of signaling pathways and changes in gene expression. Elucidating how ECs sense flow important for understanding both normal vascular function and disease. EC responses to FSS are mediated in part by a junctional mechanosensory complex consistin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
465
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 458 publications
(494 citation statements)
references
References 23 publications
14
465
2
Order By: Relevance
“…In contrast to PECAM‐1, tension across VE‐cadherin does not increase under flow but VE‐cadherin is nevertheless essential for shear response (Conway et al , 2013). The role of VE‐cadherin is not clear but it most likely regulates the strength of adhesion between individual cells (Daneshjou et al , 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to PECAM‐1, tension across VE‐cadherin does not increase under flow but VE‐cadherin is nevertheless essential for shear response (Conway et al , 2013). The role of VE‐cadherin is not clear but it most likely regulates the strength of adhesion between individual cells (Daneshjou et al , 2015).…”
Section: Introductionmentioning
confidence: 99%
“…It is dispensable for embryonic development but is required for flow induced vessel remodeling and contributes to inflammatory ac tivation at regions of disturbed flow and atherosclerosis (Goel et al, 2008;Harry et al, 2008;Stevens et al, 2008). Develop ment of a molecular force sensor showed that application of flow to ECs induces piconewton force across PECAM 1 (Conway et al, 2013), while direct application of force to PECAM 1 triggers some of the same pathways that are activated by flow (Osawa et al, 2002;Tzima et al, 2005). Thus, PECAM 1 ap pears to be a true mechanotransducer for fluid shear stress.…”
Section: Intramembrane Binding Of Ve-cadherin To Vegfr2 and Vegfr3 Asmentioning
confidence: 99%
“…It is also essential for ligand independent activation of VEGFR2 by flow, though the nature of this requirement is poorly understood (Tzima et al, 2005). VEcad does not show any increase in tension after flow (Conway et al, 2013), does not activate relevant pathways when tension is applied through magnetic beads (Tzima et al, 2005), and thus does not directly transduce mechanical forces. The VEcad TMD confers binding to…”
Section: Intramembrane Binding Of Ve-cadherin To Vegfr2 and Vegfr3 Asmentioning
confidence: 99%
“…The transmission of FSS to cell-cell junctions has been suggested in previous studies, where PECAM-1 has been identified as a mechanosensor [71,81]. New findings indicate that shear stress triggers the association of PECAM-1 with vimentin, which transmits myosin-generated forces to PECAM-1 [71,81]. The magnitude of the force produced by a single myosin molecule falls in the range of 0.4-4 pN [3,76].…”
Section: Discussionmentioning
confidence: 52%